A Selection of European and American Watercolors and Drawings. - Marlborough Fine Art Ltd., London; Marlborough Galerie AG, Zürich; Marlborough Galleria d'Arte, Roma; Marlborough-Godard Ltd., Toronto (New York : Marlborough Gallery Inc., 1971)
Arp, Hans (Jean) ; Balla, Giacomo ; Baumeister, Willi ; Bayer, Herbert ; Baziotes, William ; Botero, Fernando ; Chagall, Marc ; Colla, Ettore ; Colville, Alex ; D'Arcangelo, Allan ; Diebenkorn, Richard ; van Doesburg, Theo ; Dorazio, Piero ; Dubuffet, Jean ; Ensor, James ; Feininger, Lyonel ; Fontana, Lucio ; Francis, Sam ; Genoves, Juan ; Giacometti, Alberto ; Gleizes, Albert ; van Gogh, Vincent ; Gottlieb, Adolph ; Grosz, George ; Guston, Philip ; Guys, Constantin ; Hausmann, Raoul ; Hofmann, Hans ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Klimt, Gustav ; Kline, Franz ; Kokoschka, Oskar ; de Kooning, Willem ; Krasner, Lee ; Leger, Fernand ; Lipchitz, Jacques ; Lissitzky, El ; López-Garcia, Antonio ; Marca-Relli, Conrad ; Marcoussis, Louis ; Marin, John ; Matisse, Henri ; Miro, Joan ; Modigliani, Amedeo ; Mondriaan, Piet ; Moore, Henry ; Motherwell, Robert ; Munch, Edvard ; Nicholson, Ben ; Nolan, Sidney ; Nolde, Emil ; Novelli, Gastone ; Pascin, Jules ; Perilli, Achille ; Picasso, Pablo ; Piper, John ; Pollock, Jackson ; Puni, Ivan ; Radice, Mario ; Renoir, Pierre-Auguste ; Rivers, Larry ; Rothko, Mark ; Rouault, Georges ; Schiele, Egon ; Schlemmer, Oskar ; Schwitters, Kurt ; Scialoja, Toti ; Seago, Edward ; Severini, Gino ; Signac, Paul ; Sutherland, Graham ; Tobey, Mark ; Vuillard, Edouard
Marlborough New York - London - Rome - Zurich - Toronto, [1971]
Engels
boek